Design of Antique Shop Management Information System Based on Web Using Laravel 8 - Lidya, Dona Ayu; Tisnawati, Rini (Dinasti Publisher, 2024)
Cikapundung Antique Market is a business located in Bandung that sells antiques. Because sales are still done manually, one of the traders in the market has difficulty marketing his products. The purpose of this study is to create an antique shop website using the Laravel framework that can be used to promote antiques to collectors in various regions. This study uses the waterfall method and uses the tailwind css system modeling. The results of this study will be an antique shop website software for one of the traders in the Cikapundung Antique Market which functions to expand product marketing and make consumers faster and more comfortable in interacting with them.